2022
DOI: 10.1002/macp.202200276
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Phase Behavior of Interpolyelectrolyte Complexes of PDADMAC and Hydrophobically Modified PAA (HM‐PAA)

Abstract: By combining oppositely charged polydiallyldimethylammonium chloride (PDADMAC) and sodium polyacrylate (NaPA), interpolyelectrolyte complexes (IPECs) can be formed in aqueous solution. Such IPECs are studied for rather short NaPA and under variation of the Mw of PDADMAC. The focus is on elucidating the effect of having a hydrophobic modification of the NaPA, which is introduced by having 10 mol% of the monomeric units substituted by ones carrying a dodecyl alkyl chain. This modification renders the complexes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Fares et al found R g in a PEC to be independent of salt concentration, in contrast to the typical response of individual polyelectrolytes, possibly a consequence of the high Pol + Pol – charge density (>1 M) within PECs. SANS studies of PECs report a “low q upturn,” attributable to density fluctuations approaching the 1 μm length scale, although the materials remain transparent to the eye. ,,, This long-range feature, probably not a result of thermal fluctuations, as it changes little with temperature (Figure S4), may be due to weak microphase separation between deuterated and nondeuterated polymers. The negligible temperature dependence of coil size in Figure S4 is similar to that found in neutral polymers under θ-conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fares et al found R g in a PEC to be independent of salt concentration, in contrast to the typical response of individual polyelectrolytes, possibly a consequence of the high Pol + Pol – charge density (>1 M) within PECs. SANS studies of PECs report a “low q upturn,” attributable to density fluctuations approaching the 1 μm length scale, although the materials remain transparent to the eye. ,,, This long-range feature, probably not a result of thermal fluctuations, as it changes little with temperature (Figure S4), may be due to weak microphase separation between deuterated and nondeuterated polymers. The negligible temperature dependence of coil size in Figure S4 is similar to that found in neutral polymers under θ-conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Tis method of postpolymerization modifcation of PAA has its own advantages in selecting diferent photosensitive properties and controlling the number and position of photosensitive functional groups. However, some undesirable side reactions are inevitable during the modifcation [53][54][55]. Moreover, because it requires extra steps to introduce photosensitive groups, it causes unnecessary waste of time and cost.…”
Section: Methods Of Postpolymerization Modifcation Of Paamentioning
confidence: 99%
“…Lately, in our group, Kuzminskaya et al [18] reported a study about interpolyelectrolyte complexes of PDADMAC and PA, which mainly focused on the effect of the hydrophobic modification of PA on the structure and phase behaviour of complexes formed with PDADMAC, covering a wide range of molecular weight. The hydrophobic modification of PA was obtained by having 10 mol% monomeric units substituted by ones from a dodecyl alkyl acrylate chain.…”
Section: Introductionmentioning
confidence: 99%